Google Drive sebagai Alternatif Penyimpanan Arsip Digital Dokumen Akreditasi Perpustakaan (Best Practice Pada Perpustakaan IAIN Salatiga) - Ifonilla Yenianti (Institut Agama Islam Negeri Salatiga, 2021)
Google Drive is used as an alternative for storing digital archives for library accreditation forms at State Institute of Islamic Study (IAIN) Salatiga Library. This study uses a qualitative descriptive approach with the methods of observation, interviews and documentation. The informants in this study were the head of the library and librarian at IAIN Salatiga. The purpose of this research is to find out how to manage digital archives accredited by IAIN Salatiga library using Google Drive. The results of this study indicate that the management of digital archives for the accreditation of IAIN Salatiga library using Google Drive is by adjusting the template for the accreditation form for the college library. The library website is a link to show digital physical evidence of accreditation forms located on Google Drive. Meanwhile, the obstacles faced in managing the archives of IAIN Salatiga library accreditation forms are technical and non-technical obstacles encountered by librarians in the implementation of the preparation of digital physical evidence of library accreditation forms.